Real-Time Computer-Aided Composition with bach. - Agostini, Andrea; Ghisi, Daniele (Contemporary Music Review, 2013)
Environments for computer-aided composition (CAC), allowing generation and transformation of symbolic musical data, are usually counterposed to real-time environments or sequencers. The counterposition is deeply methodological: in traditional CAC environments interface changes have no effect until a certain ‘refresh’ operation is performed whereas real-time environments immediately react to user input. We shall show in this article that this distinction is by no means natural and that interactivity is an essential performative aspect of the musical discovery process. The reunification of the performative and speculative aspects is obtained via a Max library namedbach: automatic composer’s helper, which is a set of tools for symbolic processing and graphical music representation, designed to take advantage of Max's facilities for sound processing, real-time interaction and graphical programming.